2016
DOI: 10.1093/jnci/djv360
|View full text |Cite|
|
Sign up to set email alerts
|

CAPG and GIPC1: Breast Cancer Biomarkers for Bone Metastasis Development and Treatment

Abstract: Background:Bone is the predominant site of metastasis from breast cancer, and recent trials have demonstrated that adjuvant bisphosphonate therapy can reduce bone metastasis development and improve survival. There is an unmet need for prognostic and predictive biomarkers so that therapy can be appropriately targeted.Methods:Potential biomarkers for bone metastasis were identified using proteomic comparison of bone-metastatic, lung-metastatic, and nonmetastatic variants of human breast cancer MDA-MB-231 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 36 publications
3
84
0
1
Order By: Relevance
“…Its overexpression in cancer has been correlated with the mechanisms of cell migration and invasiveness, and more recently has been associated with breast cancer progression and bone metastases formation [130]. In our samples, we detected 2 isoforms, one of which with an icrease of 19.7 folds, versus non-tumoral tissues expressing this protein.…”
Section: Gelsolin-like Capping Protein Capg (Capg)mentioning
confidence: 53%
“…Its overexpression in cancer has been correlated with the mechanisms of cell migration and invasiveness, and more recently has been associated with breast cancer progression and bone metastases formation [130]. In our samples, we detected 2 isoforms, one of which with an icrease of 19.7 folds, versus non-tumoral tissues expressing this protein.…”
Section: Gelsolin-like Capping Protein Capg (Capg)mentioning
confidence: 53%
“…75 Remarkably, this paper was the first to identify MCP as cancer biomarker. Other studies on different human malignancies [76][77][78][79][80] validated MCP as a cancer biomarker, further supporting the use of dogs as useful models for human cancer. Studies on the serum proteome changes of canine lymphoma have been carried out by combining ion exchange chromatography and surface-enhanced laser desorption ionisation (SELDI) mass spectrometry.…”
Section: View Article Onlinementioning
confidence: 73%
“…Clinical studies concerning on risk factors of BC bone metastases were limited. 26 Our previous study identified that lymph node metastases and ESR status were independent risk factors in predicting BC spine metastases. 27 Besides, Chen et al 28 indicated that axillary lymph node metastases and the concentrations of CA125, CA153, ALP, and hemoglobin were independent risk factors for BCBM.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical studies concerning on risk factors of BC bone metastases were limited . Our previous study identified that lymph node metastases and ESR status were independent risk factors in predicting BC spine metastases .…”
Section: Discussionmentioning
confidence: 99%